Perbedaan Indeks Karies (DMF-T/def-t) Anak dengan Retardasi Mental Ringan dan Sedang di SLB Negeri 1 Badung - Audrey Calista Putri; Luh Wayan Ayu Rahaswanti; Mia Ayustina Prasetya (School of Dentistry Faculty of Medicine Udayana University, 2022)
Background: Children with mental retardation have higher incidence of periodontal disease and lower oral hygiene than normal children. Low levels of oral and dental health of children with mental retardation can cause other oral problems. The most common teeth and mouth problem in children with mental retardation is caries. The aim of this study is to determine the differences in mean caries index in children with mild and moderate mental retardation. Methods: The design of this study was observational with a comparative cross-sectional study design. The sample selection was done by stratified random sampling, which was done based on the existing class strata with a total sample of 64 students by intraoral screening procedure. Results: The result of this research indicated that in elementary school students, the group of children with mild mental retardation obtained a def-t index of 3.2 ± 5.03 (medium) and DMF-T index of 1.5 ± 1.22 (low). Meanwhile, in the group of children with medium mental retardation was recorded a def-t index of 4.1 ± 2.30 which (medium) and DMF-T amounted to 3 ± 2.27 (medium). In junior / high school students, the group of children with mild mental retardation obtained a DMF-T index of 1.9 ± 1.48 (low) and children with mental retardation was recorded DMF-T index of 4.3 ± 2.91 (medium). Conclusion: There was a significant difference in DMF-T of junior / high school students (permanent dentition) in which DMF-T children with mild mental retardation were lower than children with moderate mental retardation, but no significant difference in def-t and DMF- T in elementary school students (mixed dentition) with mild and moderate mental retardation. Latar Belakang: Anak dengan retardasi mental memiliki tingkat kejadian penyakit periodontal yang lebih tinggi serta oral hygiene yang lebih rendah dibandingkan anak normal. Rendahnya tingkat kesehatan gigi dan mulut anak dengan retardasi mental dapat menimbulkan masalah rongga mulut lainnya. Masalah gigi dan mulut yang paling banyak ditemui pada anak dengan retardasi mental adalah karies. Adapun tujuan dari penelitian ini adalah untuk mengetahui perbedaan rerata indeks karies pada anak dengan retardasi mental ringan dan sedang. Metode: Desain penelitian ini adalah observasional dengan rancangan penelitian comparative cross-sectional. Pemilihan sampel dilakukan dengan cara stratified random sampling, yaitu dilakukan berdasarkan strata kelas yang ada dengan total sampel 64 siswa melalui prosedur screening intraoral. Hasil: Hasil penelitian menunjukkan bahwa pada siswa SD, kelompok anak dengan retardasi mental ringan didapat indeks def-t sebesar 3.2 ± 5.03 (sedang) dan indeks DMF-T sebesar 1.5 ± 1.22 (rendah). Sementara itu, pada kelompok anak dengan retardasi mental sedang tercatat indeks def-t sebesar 4.1 ± 2.30 (sedang) dan DMF-T sebesar 3 ± 2.27 (sedang). Pada siswa SMP/SMA, kelompok anak dengan retardasi mental ringan didapat indeks DMF-T sebesar 1.9 ± 1.48 (rendah) dan anak dengan retardasi mental sedang tercatat indeks DMF-T sebesar 4.3 ± 2.91 (sedang). Simpulan: Terdapat perbedaan signifikan pada DMF-T siswa SMP/SMA (permanent dentition) dimana DMF-T anak dengan retardasi mental ringan lebih rendah dibandingkan anak dengan retardasi mental sedang, tetapi tidak ada perbedaan signifikan indeks def-t maupun DMF-T pada siswa SD (mixed dentition) dengan retardasi mental ringan dan sedang.